Frontline employees' views on organisational factors that affect the delivery of service quality in call centres - Dean, A.; Rainnie, Alistair (Emerald Group Publishing Limited, 2009)
Purpose - This paper aims to report on a study that investigated employees' views on the organizational factors that affect their ability to deliver service quality to customers. The study is important because call centres represent unique work environments and they have not been used in the development of service quality theory. Design/methodology/approach - Ten focus groups of frontline employees who work in a telecommunications call center in Australia were conducted. Data were subjected to content analysis. Findings - Nine major themes were identified. Some of these themes are evident in theory arising from service quality gaps, service climate, and service profit chain studies. Other themes include whether managers emphasize sales or efficiency, rather than service quality; approaches to performance monitoring and feedback, role and productivity demands, quality assurance regimes, and employees' experiences of service encounter stress. Research limitations/implications - The findings suggest that various factors from prior work need to be integrated and extended to enhance service quality in call centers. However, data were collected from only one call center. Practical implications - The present study suggests that to deliver high levels of service quality, call center managers need to rethink their approaches to productivity and performance management, and hiring and supporting the "right" service staff. Originality/value - This paper re-examines service quality in the specific context of call centers. It provides and organizational focus and complements recent work that has tested the role of employee attitudes in service quality studies. This paper concludes with a model for testing.